Transformasi Sistem Informasi Menjadi Sistem Cerdas Untuk Meningkatkan Pengambilan Keputusan Dan Efisiensi - Ikke Yamalia; Eka Martyani (Nolsatu Publisher, 2026)
The industrial world and information systems are undergoing a major shift in management practices. Growing and diverse user demands have driven information systems to evolve from passive data management into intelligent systems that assist organizational management in decision-making processes. This research aims to analyze the evolution of information systems, from conventional models to the implementation of Artificial Intelligence (AI) based systems within organizations. The findings indicate that the transformation of information systems is not merely a software update, but a paradigm shift: from passive systems reliant on manual input (Conventional Phase), to systems capable of integrated workflows (Automated Phase), and finally to systems that can learn and provide independent recommendations (Intelligent System Phase). The primary finding of this study is that the transition to intelligent systems significantly enhances operational efficiency. However, this must be balanced with high data quality as a reliable information source and supported by the readiness of human resources. In conclusion, information systems in the digital era have transformed from simple administrative tools into essential strategic partners that help organizations navigate data complexity and improve decision-making.